"AmeriKenyan": Lived Acculturation and Ethnic Identification of Kenyan Natives During Their Youth. (September 2022) - Onwong'a, Jana R.; Slaten, Christopher D.; McClain, Shannon
This qualitative study investigated the immigration, acculturation process, and ethnic identity experiences of six Kenyan emerging adults who immigrated to the United States during their adolescent years. Themes emerged from the data to describe their (a) immigration experience, (b) acculturation process into an individualistic culture with more of a Western worldview, (c) ethnic and racial identities, and (d) emotional response and coping. Subthemes and additional factors illustrated their experience as it relates to social life, academics, cultural context, family values, and more. Implications for multicultural psychology research and practice are addressed.